2022
DOI: 10.18421/sar53-03
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Refractive Index and Reflectance of Sodium Metal Based on Drude's Theory Using MATLAB as an Alternative for Optics and Astrophysics Lectures

Abstract: This study aims to simply examine the relationship between optics and astrophysics by visualizing the refractive index and reflectance of sodium metal based on Drude's theory using MATLAB. Sodium metal is used in this study because it is an alkaline metal found on Earth which is a life-supporting element. MATLAB is used to visualize the refractive index and reflectance of sodium metal based on Drude's theory because it is one of the software that is often used by students in supporting optics and astrophysics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…5), it was found that the size of individual particles ranged from 80-8000 d.nm, with a measurement intensity of 4-33%. A special problem in particle size distribution analysis is the determination of over and undersized particles [13], [16]. These are small partsof particles that are significantly larger or significantly smaller than the bulk of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…5), it was found that the size of individual particles ranged from 80-8000 d.nm, with a measurement intensity of 4-33%. A special problem in particle size distribution analysis is the determination of over and undersized particles [13], [16]. These are small partsof particles that are significantly larger or significantly smaller than the bulk of the sample.…”
Section: Resultsmentioning
confidence: 99%